The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12887-020-02236-0
|View full text |Cite
|
Sign up to set email alerts
|

Veganism and paediatric food allergy: two increasingly prevalent dietary issues that are challenging when co-occurring

Abstract: Vegan dietsdefined as the exclusion of all foods of animal origin from the diet-are becoming popular. In recent years, the prevalence of food allergy has also increased, and disproportionately affects children. When vegan diets and food allergy co-occur, this combination can be challenging and pose risks of nutritional deficiencies, particularly during childhood. In this paper, we aim to summarise the major concerns regarding vegan diets and food allergy, review the literature on this topic, and provide some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 135 publications
(188 reference statements)
0
17
0
1
Order By: Relevance
“…On the other hand, vegan patterns have globally risen during the last several years, including in FA pediatric patients [31,32]. Among the different motivations of plant-based dieters, the aversion to animal products due to moral and ethical reasons is highlighted [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, vegan patterns have globally risen during the last several years, including in FA pediatric patients [31,32]. Among the different motivations of plant-based dieters, the aversion to animal products due to moral and ethical reasons is highlighted [33].…”
Section: Discussionmentioning
confidence: 99%
“…The management of food allergies and dietary avoidance presents several challenges for pediatric dietitians and other healthcare providers [43]. Health professionals who assess FA patients should include nutrition therapy to ensure the adequate intake of nutrients as well as nutritional education with comprehensive information about allergenic ingredients for their avoidance [31,44]. The American Academy of Pediatrics established as a critical issue the improving of the education and training of all stakeholders for recognizing and managing, as well as preventing, allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…There was a correlation between the number of foods excluded and the number of people with nutrient intakes below the reference range, but only for the group with no FA (Spearman r = 0.5074, p = 0.064). The challenge of ensuring dietary and nutritional needs are met in those with food allergy is exacerbated by increased exclusion of foods due to lifestyle choices such as vegetarianism and veganism ( 13 ). In the cohort studied, 9/29 (31%) were avoiding meat, two of whom were also avoiding fish.…”
Section: Discussionmentioning
confidence: 99%
“…However, many will also be avoiding multiple foods due to suspected or actual food intolerance, such as those diagnosed with Pollen Food Syndrome (PFS) or Oral Allergy Syndrome. The nutritional status of adults with food allergy or intolerance could be further compromised if those individuals are following a vegetarian or vegan lifestyle, as diets may be low in vitamin B12, vitamin D, zinc, calcium and iron ( 13 ). A study on the nutritional profile of children and adults with a milk allergy reported that there were nutritional deficiencies, especially if more than one food was being avoided ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probably due to processed foods, industrial preparation procedures, pollution, and the introduction of food additives, FAs have seen a steady increase, particularly in developed countries [6][7][8][9][10][11][12][13]. As risk factors for food allergies, we also mention genetic predisposition, which is proven by the fact that FA is more common in people with atopy.…”
Section: Introductionmentioning
confidence: 99%